2020
DOI: 10.1097/md.0000000000022052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of reversible splenial lesion syndrome in Chinese adults

Abstract: Reversible splenial lesion syndrome (RESLES) is a clinico-radiological entity that defines a reversible lesion in the splenium of the corpus callosum (SCC) on magnetic resonance imaging (MRI). The clinical and radiological characteristics of RESLES are poorly defined and most RESLES literature is in the form of case reports. We reviewed the clinical and radiological data from 11 RESLES patients in order to more clearly describe the characteristics of this disorder in adults. Patients included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Among the known causes of RESLES, the most common ones include infections, epilepsy, high-altitude cerebral oedema, as well as nutritional and metabolic factors including hypoglycaemia and hypernatraemia, systemic lupus erythematosus etc., 5 Incidences of RESLES are closely associated with infections, particularly viral infections, such as measles, herpes virus, 6 Epstein-Barr virus, dengue virus, varicella-zoster virus, and adenovirus. 6 The RELES has diverse clinical features, including headaches, seizures, loss of consciousness, mental abnormalities, dizziness, obtundation and syncope. 7 , 8 Most patients have good prognostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the known causes of RESLES, the most common ones include infections, epilepsy, high-altitude cerebral oedema, as well as nutritional and metabolic factors including hypoglycaemia and hypernatraemia, systemic lupus erythematosus etc., 5 Incidences of RESLES are closely associated with infections, particularly viral infections, such as measles, herpes virus, 6 Epstein-Barr virus, dengue virus, varicella-zoster virus, and adenovirus. 6 The RELES has diverse clinical features, including headaches, seizures, loss of consciousness, mental abnormalities, dizziness, obtundation and syncope. 7 , 8 Most patients have good prognostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 5 However, recent reports remark on the presence of extracallosal lesions frequently in patients with RESLES. 4 6 Zhang et al reported extracallosal lesions in four of their eight patients with RESLES and they discussed that these lesions may be associated with unfavorable prognosis. 4 Contrasting with this observation, the prognosis of our patient was excellent, such that she recovered completely in a few days following transfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Reversible splenial lesion syndrome (RESLES) is a clinical radiological syndrome characterized by the presence of a focal lesion often involving the central area of the splenium of the corpus callosum (SCC). The most common neurological symptoms of this syndrome include headache, dizziness, seizure, disturbance of consciousness, and mental abnormality ( 1 , 2 ). Generally, these symptoms are reversible in most cases, and patients typically recover in a few days or weeks.…”
Section: Introductionmentioning
confidence: 99%